Fermented Seed of Parkia biglobosa (Jacq.) Benth (African Mustard) Diet Prevents Myocardial Infarction in Rat - Kodjo, Adi; Kossi, Metowogo; Kwashie, Eklu-Gadegbeku; Courdjo, Lamboni; Gado, Napo-Koura; Kodjo, Aklikokou A.; Messanvi, Gbeassor (Pakistan Journal of Nutrition, 2013)
Hypertension and diabetes are traditional major common risk factors of ischemic heart diseases. Antidiabetic and anhypertensive property of Parkia biglobosa (PB) are well documented. In our previous study, we demonstrated that stem bark of PB possessed cardioprotective effects in rats. Fermented seeds of PB (African mustard) is a natural nutritional condiment frequently used to season sauces in African diets. This study evaluated fermented seed of PB (FSPB) dietary preventing heart attacks in isoproterenol (ISO) induced Myocardial Infarction (MI). Four groups of five Sprague dawley rats of each were used. Control group, received the saline solution as vehicle (5ml/kg) per os (p.o) daily, for 15 days and was injected subcutaneously with vehicle (2ml/kg) at an interval of 24 hours, on day 14 and 15. Infarcted group received vehicle p.o and was injected subcutaneously ISO (100 mg/kg) as in control group. FSPB pre-treated groups received p.o FSPB (1g eq mv/kg and 2g eq mv/kg respectively) daily, for 15 days and was injected subcutaneously ISO (100mg/kg). ISO has induced MI, characterized by significant (p